A Participative Process of Strategy-Making and Firm Performance in Iranian Pharmaceutical Companies: Strategy-Making and Firm Performance in Iranian Pharmaceutical Companies - Abolfazli, Seyed Abolfazl; Mohammadzadeh, Mehdi; Peiravian, Farzad; Sharifnia, Seyed Hesam (Iranian Journal of Pharmaceutical Sciences, 2018)
Pharmaceutical companies are regarded as principal contributors to national economies all over the world owing to their substantial assistance to public health system; GDP, employment, and market growth. Consequently, pharmaceutical managers must take the necessary steps to improve strategy-making and firm performance. This study investigates the relationship between four conventional modes of strategy-making process and performance in pharmaceutical companies in Iran. This paper argues that small or knowledge-based pharmaceutical companies, similar to large pharmaceutical companies, place differing emphasis on strategy-making and could apply different approaches to strategy-making. Furthermore, the present research offers an explanation of the nature of these processes in pharmaceutical companies and hypothesizes how they are related to firm performance. It then describes the results of an empirical study on the strategy-making processes of pharmaceutical companies in Iran. Analysis of the data obtained from 125 pharmaceutical companies indicates that participative approaches to strategy-making exist in these pharmaceutical companies and could have a significant and strong relationship with firm performance.